Investigating the sustainability of a food system by system dynamics approach. (3rd November 2020) - Amiri, Alireza; Mehrjerdi, Yahia Zare; Jalalimanesh, Ammar; Sadegheih, Ahmad
Food is one of the essential human needs, from birth to death. The existence of sustainable systems that satisfy such requirements is always critical for the survival of the human race. This study investigates the sustainability of a food system using the system dynamics approach. The proposed model is applied to a food system in Iran. For this, the key factors affecting the production of wheat, the primary food resource in Iran, were analysed. Based on the history of these factors and related research works, causal loop diagrams were depicted. Then, the problem was simulated by drawing the flow diagram. After the model validation, several scenarios were proposed for sustainable wheat production. Reducing the use of chemical fertilisers and increasing the use of organic fertilisers, while in the short term, reduce the production, in a long time, by improving soil quality, bring about an increase in cropping sustainability and wheat production.